Integrated Network Pharmacology and Experimental Verification to Explore the Molecular Mechanism of Hedysarum Multijugum Maxim–Curcumae Rhizoma Herb Pair for Treating Non-Small Cell Lung Cancer - Hu, Shaopu; Ge, Mengxue; Zhang, Shuixiu; Jiang, Min; Hu, Kaiwen; Gao, Lei (Frontiers in Oncology, 2022)
Background Hedysarum Multijugum Maxim–Curcumae Rhizoma (HMMCR), a well-known herb pair in traditional Chinese medicine (TCM), has been widely used for the treatment of various cancers. However, the active components of HMMCR and the underlying mechanism of HMMCR for non-small-cell lung carcinoma (NSCLC) remain unclear. Methods Active ingredients of HMMCR were detected by liquid chromatography electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS). On this basis, potential targets of HMMCR were obtained from SwissTargetPrediction database. NSCLC-related targets were collected from four public databases (GeneCards, OMIM, TTD, and PharmGkb). The drug ingredients–disease targets network was visualized. The hub targets between HMMCR and NSCLC were further analyzed by protein–protein interaction (PPI), Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses. Subsequently, the results predicted by network pharmacology were further validated via in vitro experiments. Results A total of 181 compounds were identified from the aqueous extract of HMMCR. Through network analysis, a compound–target network including 153 active ingredients of HMMCR and 756 HMMCR-NSCLC co-targets was conducted; 6 crucial compounds and 62 hub targets were further identified. The results of KEGG enrichment analysis showed that PI3K/Akt signaling pathway may be the critical pathway of HMMCR in the treatment of NSCLC. The in vitro experiments indicated that HMMCR inhibits the proliferation and migration of NSCLC cells via inactivation of the PI3K/Akt signaling pathway, consistent with the results predicted by network pharmacology. Conclusion Integrating LC-ESI-MS/MS, network pharmacology approach, and in vitro experiments, this study shows that HMMCR has vital therapeutic effect on NSCLC through multi-compound, multi-target, and multi-pathway, which provides a rationale for using HMMCR for the treatment of NSCLC.